The Effect of Mordan on The Result of Dyeing Rayon Twill Fabric with Longan Leaf Extract (Dimocarpus Longan L.) - Annisa, Zetri; Adriani, Adriani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research is motivated by the use of longan leaves as a natural dye because of the tannin and flavonoid content that can produce color. This study aims to describe the color name (hue), color evenness, and color fastness to washing produced from dyeing rayon twill fabric with longan leaf extract (Dimocarpus Longan L.) with the influence of alum mordant, tunjung, and betel lime. This type of research uses an experimental research type with primary data from 18 panelists through a questionnaire. Data were analyzed using the Friedman K-Related Sample test with SPSS version 26. This study produced a color name without mordant: Off-White Lemon #F4E5AA, average color evenness, color fastness to washing 1x and 2x slightly changed/reduced, 3x washing changed/reduced. The effect of alum mordant produces Pale Golden #EBDC98, average color evenness, color fastness to washing 1x, 2x, and 3x slightly changed/reduced. The effect of tunjung mordant produces Dark Gray (13% white) #222222, the color evenness is quite even, the color fastness to washing 1x, 2x, and 3x changes/decreases slightly. The effect of betel lime mordant produces Golden Sundace #C2A66C, the color evenness is even, the color fastness to washing 1x does not change at all, 2x and 3x washings change/decrease slightly. The result of the Friedman K-Related Sample test for color evenness is 0.000 <0.05 = Ho is rejected, meaning there is a significant difference in color evenness. The results of the Friedman K-Related Sample test for color fastness to washing without mordant, alum, and lime were 0.000 <0.05 = Ho was rejected, tunjung was 0.001 <0.05 = Ho was rejected, meaning that there was a significant difference in color evenness and color fastness to washing due to the influence of tunjung, lime, and alum mordants on the results of dyeing twill rayon fabric with longan leaf extract (Dimocarpus Longan L.).